Exploring variation in parental worries about HPV vaccination: a latent-class analysis. Issue 7 (3rd August 2019) - Gilkey, Melissa B.; Mohan, Divya; Janssen, Ellen M.; McRee, Annie-Laurie; Kornides, Melanie L.; Bridges, John F. P.
ABSTRACT: Background . Prior research has identified diverse worries that parents have about HPV vaccination. We sought to understand how parents prioritize worries and to identify subgroups of parents according to shared patterns of worry. Methods . We surveyed a national sample of 431 U.S. parents of adolescents who reported never having talked to their child's healthcare provider about HPV vaccination. Parents completed a best-worst scaling experiment designed to prioritize 11 common worries about HPV vaccination. The experiment used a balanced incomplete block design to present 11 choice tasks consisting of repeated subsets of worries. We used conditional logistic regression to prioritize worries and latent class models with 1–10 classes to identify subgroups of parents with shared worries. Results . Parents most often worried about long-term side effects of HPV vaccination, which about one-third (36%) ranked as their top worry. Other common top-ranked worries were how new the vaccine is (12%), motives of drug companies (12%), short-term side effects (10%), and that it may be unnecessary (10%). Latent class analyses suggested a relatively large number of distinct worry profiles, with most classes characterized by a worry about long-term side effects in combination with one other worry. Discussion . Our findings suggest that providers should be prepared to address concerns about long-term side effects, as this worry was prioritized across many subgroups of parents. However, to best address worry, a tailored, rather than targeted, communication approach may be needed.